New digital tool to facilitate subcutaneous insulin therapy orders: an inpatient insulin dose calculator. Issue 1 (December 2015) - Toyoshima, Marcos; Souza, Alexandre; Admoni, Sharon; Cukier, Priscilla; Lottenberg, Simão; Latronico, Ana; Nery, Márcia
Abstract Background Inpatient hyperglycemia is associated with adverse outcomes in hospitalized patients, with or without known diabetes. The adherence to American College of Endocrinology and American Diabetes Association guidelines recommendations for inpatient glycemic control is still poor, probably because of their complexity and fear of hypoglycemia. Objective To create software system that can assist health care providers and hospitalists to manage the insulin therapy orders and turn them into a less complicated issue. Methods A software system was idealized and developed, according to recommendations of major consensus and medical literature. Results HTML software was developed to be readily accessed from a workstation, tablet or smartphone. Standard initial daily total dose of insulin was 0.4 units/kg and could be modified by distinct factors, such as chronological age, renal and liver function, and high dose corticosteroids use. Insulin therapy consisted of basal, prandial and correction insulin according to nutritional support, glycemic control and outpatient treatment for diabetes. Human insulin or insulin analogues could be options for insulin therapy. Sensitivity factor was based on 1800 Rule for rapid-acting insulin and the 1500 Rule for short-acting insulin. Insulin-naïve patients with initial BG level less than 250 mg/dL were considered to have an initial step-wise approach with prandial and correction insulin. The calculator system has allowed insulin dose readjustments periodically, according to daily average blood glucose measurements. Conclusion We developed software that can be a useful tool for all public hospitals, where generally human insulin is the only available.